Analisis Partisipasi Masyarakat Lamaholot Dalam Menjunjung Tinggi Nilai Ritual Adat Lewak Tapo Di Desa Keluwain Kecamatan Kelubagolit Kabupaten Flores Timur - Felix, Ariston; Kleden, Marianus; Indriyati (JAP UNWIRA, 2025)
AbstractThe lewak tapo traditional ritual ceremony is a Lamaholot traditional ritual that is carried out specifically on the island of Adonara as a symbol of recovery and cleansing for all the wrongs and sins that have been committed by previous ancestors and the victim himself because of a death that is considered unnatural or a bloody event (mata reket). The purpose of this study is to determine the extent of community participation as well as the supporting and inhibiting factors that occur in the lewak tapo traditional ritual in Keluwain Village, Kelubagolit Sub-district, East Flores Regency. This research adopts the theory of community participation according to Uphoff et al (1979) cited in Anggitirani (2020) where there are four stages of community participation that are the focus of this research, namely the decision-making stage, the programme implementation stage, the stage of enjoying the results, and the assessment or evaluation stage. The research method used is a qualitative research method with a descriptive approach and the types of data used are primary data and secondary data. The data collection techniques used were observation, interviews, and documentation. Based on the results of field observations, the researcher can conclude that the Keluwain Village community participated in the programme implementation stage, enjoying the results, and assessment or evaluation. Meanwhile, the planning stage only involves families together with traditional elders such as landlords (bele lewo), healers (ata molang), and traditional priests (ata mu'a). Community participation is also influenced by the values contained in the lewak tapo traditional ritual such as religious values/beliefs, truth/honesty values, socio-cultural values, solidarity/humanity values, deliberation/consensus values, and satisfaction values.